2008
DOI: 10.1111/j.1708-8240.2008.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Considerations for Restoring Mandibular Incisors With Porcelain Laminate Veneers

Abstract: Porcelain laminate veneers have been proven to be a successful treatment modality for maxillary incisors in clinical practice and in controlled clinical studies. However, the data in clinical studies on the success of veneers for restoring mandibular incisors are limited. Clinically, the successful restoration of mandibular incisors with porcelain laminate veneers is one of the more challenging procedures in all of esthetic restorative dentistry. Limited coronal dimensions, the small amount of enamel available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Data from clinical studies on the success rates of veneer restorations of mandibular teeth are limited, as most published studies include only a small number of mandibular ceramic veneers, if any. [1][2][3]5,11 In this study, a relatively high percentage of the veneers were placed on mandibular incisors (35%). The statistical analyses identified no significant association between the survival (P 5 .56) or success (p 5 .30) of the restoration and the jaw position of the veneers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from clinical studies on the success rates of veneer restorations of mandibular teeth are limited, as most published studies include only a small number of mandibular ceramic veneers, if any. [1][2][3]5,11 In this study, a relatively high percentage of the veneers were placed on mandibular incisors (35%). The statistical analyses identified no significant association between the survival (P 5 .56) or success (p 5 .30) of the restoration and the jaw position of the veneers.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]5 The heterogeneity of the reported data is attributed to the different failure criteria used and different preparation designs (with/without incisal overlap), adhesive luting techniques and patient-related factors (eg, age, gender, and bruxism). [5][6][7][8][9][10][11][12][13] Higher failure rates have been reported in clinical studies, especially in patients with symptoms of bruxism activity. 12,13 Among other factors, the amount of exposed dentin has been discussed as a risk factor for ceramic veneer restoration clinical failure.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the numerous restorative techniques capable of mimicking natural teeth, ceramic veneers are known for their longevity, color stability and biocompatibility. In some cases, they can be also minimally invasive, and even without the need for dental preparation, as some ceramics such as lithium disilicate enable the performance of thin restorations (0.1 to0.7 mm) [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Although direct composite restorations have the advantages of conservation of the tooth structure, low cost, reversibility, and a relatively simple technique [4], it was reported that they have a high failure rate [5] for extensive tooth reconstruction due to secondary caries, loss of restoration, pigment impregnation, fracture, marginal defects [6], or a high degree of color instability [7]. With the increased esthetic demands and the improvement in dental materials, the use of all-ceramics for indirect esthetic restorative procedures in recent years has increased [8,9]. The introduction of ceramic veneers was in 1983 [10].…”
Section: Introductionmentioning
confidence: 99%